Pengaruh Kebijakan Suku Bunga Sertifikat Bank Indonesia (SBI) terhadap Fungsi Intermediasi Perbankan Melalui Suku Bunga Di Sektor Keuangan - Oktavia, Rina; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is to know the effect of interests rate policy of SBI towards the banks’ intermadiation function through the interest rates of credit and deposit variables. The objects in this research divided based on the bank’s ownership, which are the banks owned by the government, the banks owned by private, and the banks owned by local government. Thus will be known the bank’s response based on the bank’s ownership towards the central bank monetary policy using SBI instrument. This research using path analysis with SBI’s,deposits,and credits ( capital, investment and consumption) interest rates, and also the Loan to Deposit Ratio. Empirical studies showing that the SBI’s Interest rate policy gives more influence towads the government-owned banks. Furthermore,this research found that the composition of Third-party funds (DPK) has an influence to the banks response and distribution of credit. Keywords: SBI’s interest rate, deposit interest rate, creditinterest rate, Loan to Deposit Ratio, Path Analysis